Fernando Peña - A phylogenetic study of COVID-19 data from Aragon and Catalonia over a year: learning Bioinformatics during a world pandemic - Peña, Fernando (Jornada de Jóvenes Investigadores del I3A, 2022)
A phylogenetic study of COVID-19 data from Aragon and Catalonia over a year: learning Bioinformatics during a world pandemic